Refined foraminiferal biostratigraphy of upper Wordian, Capitanian, and Wuchiapingian strata in Hambast Valley, Abadeh region (Iran), and paleobiogeographic implications. (10th March 2020) - Shahinfar, Sima; Yousefi Yeganeh, Bizhan; Arefifard, Sakineh; Vachard, Daniel; Payne, Jonathan L.
Abstract : The foraminiferal biostratigraphy and precise geological ages of the late Wordian, Capitanian, and Wuchiapingian strata in the Abadeh region of Iran have remained poorly constrained, despite evidence that they contain one of the most complete marine records of this important time interval. The purpose of this study is to provide a more complete documentation about the foraminiferal community preserved in these deposits, to assess their correlation with other Tethyan shelves, and to address implications for paleobiogeography. The foraminifers and calcareous algae from two measured stratigraphic sections allowed us to re‐evaluate the biostratigraphy of the poorly studied upper part of the Surmaq Formation and the entire Abadeh Formation in the Hambast Valley, Abadeh region, Iran. Foraminiferal assemblages consist of 72 species belonging to 34 genera. Calcareous algae and botanical incertae sedis include seven species from four genera, of which two species are new: Eogoniolina kordeae n. sp. and Sphairionia stellata n. sp. Four foraminiferal biozones are identifed in both sections: upper Wordian‐lower Capitanian Altineria bacillaeformis ‐ Baisalina pulchra ‐" Hemigordius " aff. japonicus ‐ Sphairionia stellata Zone, upper Capitanian Baisalina cf. guizhouensis ‐ Hemigordius giganteus Zone, uppermost Capitanian Hemigordius irregulariformis Zone, and Wuchiapingian Pseudodunbarula ‐ Codonofusiella kwangsiana ‐ Reichelina cf. changhsingensis Zone. According to the foraminiferal assemblages, the beginning of the Wuchiapingian is placed at the lower part of the subunit 4b, which is contrary to the previous study reporting the base of unit 5 of the Abadeh Formation or the base of the unit 6 of the Hambast Formation as lower Wuchiapingian. Coeval biozones have been described in Transcaucasia in the former USSR. The similarity of foraminiferal assemblages in the Abadeh region and Transcaucasia reveals a proximity between these two regions, at least during Capitanian and Wuchiapingian time. Furthermore, the resemblance of foraminiferal faunas between Abadeh region and South China is more likely through palaeocurrent gyres, which facilitated the faunal exchange between these two regions despite their great geographic distances.